Protocol of a feasibility study for cognitive assessment of an ageing cohort within the Southeast Asia Community Observatory (SEACO), Malaysia. Issue 1 (19th January 2017) - Mohan, Devi; Stephan, Blossom C M; Allotey, Pascale; Jagger, Carol; Pearce, Mark; Siervo, Mario; Reidpath, Daniel D
Abstract : Introduction: There is a growing proportion of population aged 65 years and older in low-income and middle-income countries. In Malaysia, this proportion is predicted to increase from 5.1% in 2010 to more than 15.4% by 2050. Cognitive ageing and dementia are global health priorities. However, risk factors and disease associations in a multiethnic, middle-income country like Malaysia may not be consistent with those reported in other world regions. Knowing the burden of cognitive impairment and its risk factors in Malaysia is necessary for the development of management strategies and would provide valuable information for other transitional economies. Methods and analysis: This is a community-based feasibility study focused on the assessment of cognition, embedded in the longitudinal study of health and demographic surveillance site of the South East Asia Community Observatory (SEACO), in Malaysia. In total, 200 adults aged ≥50 years are selected for an in-depth health and cognitive assessment including the Mini Mental State Examination, the Montreal Cognitive Assessment, blood pressure, anthropometry, gait speed, hand grip strength, Depression Anxiety Stress Score and dried blood spots. Discussion and conclusions: The results will inform the feasibility, response rates and operational challenges for establishing an ageing study focused on cognitive function in similar middle-income country settings. Knowing the burden of cognitive impairment and dementia and risk factors for disease will inform local health priorities and management, and place these within the context of increasing life expectancy. Ethics and dissemination: The study protocol is approved by the Monash University Human Research Ethics Committee. Informed consent is obtained from all the participants. The project's analysed data and findings will be made available through publications and conference presentations and a data sharing archive. Reports on key findings will be made available as community briefs on the SEACO website.